2014
DOI: 10.1103/physrevb.90.144425
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence on the remanent magnetization of Fe-Ni alloys and Ni metal

Abstract: We measured the acquisition of magnetic remanence of iron-nickel alloys (Fe 64 Ni 36 , Fe 58 Ni 42 , and Fe 50 Ni 50 ) and pure Ni under pressures up to 23 GPa at room temperature. Magnetization decreases markedly for Fe 64 Ni 36 between 5 and 7 GPa yet remains ferromagnetic until at least 16 GPa. Magnetization rises by a factor of 2-3 for the other compositions during compression to the highest applied pressures. Immediately upon decompression, magnetic remanence increases for all Fe-Ni alloys while magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…The enhanced T N of h -VB can be attributed to the reduction in distances between V atoms caused by the applied compressive strain. This phenomenon has been experimentally observed in Fe 64 Ni 36 alloy, where compressive strain strengthens ferromagnetic interactions by decreasing the distances between nearest neighbor Fe atoms …”
Section: Results and Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The enhanced T N of h -VB can be attributed to the reduction in distances between V atoms caused by the applied compressive strain. This phenomenon has been experimentally observed in Fe 64 Ni 36 alloy, where compressive strain strengthens ferromagnetic interactions by decreasing the distances between nearest neighbor Fe atoms …”
Section: Results and Discussionsupporting
confidence: 58%
“…This phenomenon has been experimentally observed in Fe 64 Ni 36 alloy, where compressive strain strengthens ferromagnetic interactions by decreasing the distances between nearest neighbor Fe atoms. 71 The calculation results of ΔG H* for h-HfBO under different biaxial strains are presented in Figure 6e. It is observed that the adsorption of H* (hydrogen) on h-HfBO decreases as the biaxial compressive strain increases.…”
Section: Strain Effect On the Electronic Structures Andmentioning
confidence: 99%
“…If we simply scale the predicted values for T C of the chemically ordered case according to our obtained reduction of the ferromagnetic-paramagnetic energy difference, we obtain an estimate for the Curie temperature of chemically disordered FeNi of around 550 K, which however appears too low compared to experimental values of around 785-789 K [37,38].…”
Section: A Energetics Of the Order-disorder Transitionmentioning
confidence: 86%
“…The temperature-dependent effects of pressure have also been seen in studies of the Curie temperature of Fe3Pt [10][11]. Studies have also been performed on the acquisition of magnetic remanence of iron-nickel alloys (Fe64Ni36, Fe58Ni42, and Fe50Ni50) and pure Ni under pressures up to 23 GPa [12]. In these studies strain may accumulate irreversibly throughout the system.…”
Section: A Pt-fe Alloysmentioning
confidence: 97%